2021
DOI: 10.3390/ijms22063194
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Connexin Gap Junction and Hemichannels in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is one of the main causes of vision loss in the working age population. It is characterized by a progressive deterioration of the retinal microvasculature, caused by long-term metabolic alterations inherent to diabetes, leading to a progressive loss of retinal integrity and function. The mammalian retina presents an orderly layered structure that executes initial but complex visual processing and analysis. Gap junction channels (GJC) forming electrical synapses are present in each ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 186 publications
1
11
0
Order By: Relevance
“…Moreover, a recent study by Lyon et al identified that inflammation coupled with glycaemic damage mediates EMT of the RPE via aberrant Cx43 mediated hemichannel activity [ 50 ], whilst Peptide 5 blocked loss of ZO-1 expression and restores RPE permeability as measured by transepithelial resistance [ 125 ]. These studies further support the extensive work in the field of connexin biology and ophthalmology, which in recent years has identified a key pathological role for connexin hemichannels in ophthalmological disease [ 47 ].…”
Section: The Therapeutic Potential Of Blocking Cx43 In Diabetic Retinopathysupporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, a recent study by Lyon et al identified that inflammation coupled with glycaemic damage mediates EMT of the RPE via aberrant Cx43 mediated hemichannel activity [ 50 ], whilst Peptide 5 blocked loss of ZO-1 expression and restores RPE permeability as measured by transepithelial resistance [ 125 ]. These studies further support the extensive work in the field of connexin biology and ophthalmology, which in recent years has identified a key pathological role for connexin hemichannels in ophthalmological disease [ 47 ].…”
Section: The Therapeutic Potential Of Blocking Cx43 In Diabetic Retinopathysupporting
confidence: 72%
“…Dysregulation of hemichannel function is associated with chronic diseases, including deafness [ 39 ], brain ischaemia [ 40 ] and chronic pain [ 41 , 42 ]. The role of hyperglycaemia in regulating connexin expression [ 43 , 44 ], gap junction communication [ 45 ] and hemichannel activity [ 46 , 47 , 48 ] is well documented [ 49 ], and of the 21 isoforms known to be expressed within the human body, Cx43 has been strongly linked to the pathogenesis of multiple secondary complications of diabetes [ 43 , 50 , 51 , 52 ]. In this article, we review a role for Cx43 hemichannels in chronic inflammation and microvascular complications of diabetic nephropathy and retinopathy, ahead of exploring the therapeutic potential of hemichannel blockers in preventing disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, we found that Cx43 was distributed between c-kit + cells and SCF-expressing Müller cells, suggesting physical connection between these cells may exist. In the retina, Cx43 is expressed within the perivascular endfeet of astrocytes, Müller cells, retinal pigment epithelium and some neurons, and has been functionally associated with vascular regulation ( Gonzalez-Casanova et al, 2021 ). The regulatory role of Cx43 in the endogenous SCF/c-kit signaling pathway has not been fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…Since Cx HCs form poorly selective ion channels of high conductance, their opening leads to an influx of Ca 2+ , breakdown of the electrochemical gradient across the plasma membrane, and loss of essential metabolites. HCs are activated under pathological conditions, including oxidative stress, mechanical stretch, inflammatory processes, and low pH [61][62][63][64][65][66][67]. An exacerbated HC activity during pathological states can increase cell damage.…”
Section: Connexin Forms Gap Junction Channels and Hemichannelsmentioning
confidence: 99%